Analysis of the Mutqinin Application for Al-Qur'an Learning - Sabila, Ahda; Nugroho, Kharis (Universitas Muhammadiyah Surakarta, 2023)
Lastly, learning the Quran has developed rapidly, especially with technology adoption. One of the interesting applications that caught my attention was Mutqinin, a digital platform intended to help people from various backgrounds learn the Quran. This article analyzes it from a corner view of functionality, effectiveness, and impact on the experience of learning the Quran. This analysis begins by looking at the features of Mutqinin, which include learning methods such as tajwid, reading the Quran, and practice and evaluation. Then, the evaluation of the effectiveness of the application is carried out based on user interactivity, ease of navigation, and the quality of the content presented. The main focus of this analysis is the effect of using Mutqinin on understanding and the ability to understand the Quran. The analysis also covers technical elements such as customer support, user data security, and platform adaptability for various devices. In addition, discussions were held regarding the development of Mutqinin, which was adjusted to user feedback. This discussion aimed to emphasize improvements and enhancements that could be made to improve the quality of learning. Hopefully, this analysis will provide a comprehensive insight into the advantages and disadvantages of the Mutqinin application in learning the Quran. The results will help develop Islamic educational technology and help users choose the Quran learning platform that best suits their needs.